A Complex Nutrient Exchange Between a Gall-Forming Aphid and Its Plant Host - Chen, Xiaoming; Yang, Zixiang; Chen, Hang; Qi, Qian; Liu, Juan; Wang, Chao; Shao, Shuxia; Lu, Qin; Li, Yang; Wu, Haixia; King-Jones, Kirst; Chen, Ming-Shun (Frontiers in Plant Science, 2020)
It has been long asked whether the interaction between gall-forming insects and their host plants is merely parasitic or it may also benefit the host. Aphid Schlechtendalia chinensis induces the horned galls on Rhus chinensis. Thousands of aphids residing in the closed gall caused extreme high level of CO2 accumulation (on average 8 folds higher and up to 16 times than atmospheric levels) and excreted lots of honeydew. Our 13C isotope tracing test and gene data revealed that CO2 and honeydew produced by aphid were recycled in gall tissue via photosynthesis and glycometabolism. These results indicated that a self-nutritional circulation system evolved between aphid and gall: gall provided nutrients to aphids, in turn, aphid’s metabolites contributed carbon resource to the growth of gall. In this self-nutrient circulation, the high metabolic efficiency of galls means that minimum input is needed from the host plant to maintain aphid population growth within galls. Except for self-nutrient circulation, we also found that nutrients in gall transported to other parts of plant, demonstrated that the nutrition circulation between gall and other parts of host plant is interchangeable, as a result, leaves circumjacent gall grow well. In S. chinensis- Rhus chinensis system, the gall is a highly specialized structure that serves as a metabolic and nutrient exchange hub that benefits both aphid and its host plant, host plants provide shelters and nutrients for aphids via galls, and in turn, aphid-derived metabolites contribute nutrients to gall and host plant.